Establishing Tall Fescue and Kentucky Bluegrass Using Subsurface Irrigation and Saline Water. (1st January 2013) - Schiavon, Marco; Leinauer, Bernd; Serena, Matteo; Sallenave, Rossana; Maier, Bernd
Abstract : Subsurface capillary irrigation (SCI), drip lines surrounded by a patented membrane, is purported to conserve irrigation water by applying water more evenly and efficiently. A study was conducted at New Mexico State University from 2009 to 2011 to investigate the establishment of tall fescue ( Festuca arundinacea L.) and Kentucky bluegrass ( Poa pratensis L.) irrigated using either SCI or a sprinkler irrigation system in combination with saline (electrical conductivity [EC] = 2.8 dS m −1 ) or potable water (EC = 0.6 dS m −1 ). Tall fescue was seeded in September 2009 and in October 2010 for the second establishment experiment together with Kentucky bluegrass. Seedling density 30 d after seeding (DAS) was greater on sprinkler‐irrigated plots than on SCI plots. Generally, sprinkler‐irrigated plots achieved greater ground coverage at the end of the establishment period than SCI plots. Capillary‐irrigated plots reached 75% ground cover as fast as sprinkler‐irrigated ones in 2010 (202 and 212 DAS. respectively) but were slower in 2011. At the end of both growing seasons, higher EC levels were measured in SCI plots than in sprinkler‐irrigated plots. The highest Na concentration (26.3 mmolc L −1 ) and Na adsorption ratio (13.0) were measured on plots irrigated through SCI with saline water. Results suggest that SCI can be used to establish cool‐season turfgrass; however, grow‐in of subsurface‐irrigated turf can be delayed compared with sprinkler irrigation. Further research is needed to determine if acceptable turf quality can be maintained past establishment when using a SCI system in combination with lower quality, saline water.